Trait Specific Genetic Stocks for Clusterbean [Cyamopsis tetragonoloba (L.) Taub.] Improvement - Mahla, H.R.; Sharma, R.; Rathore, V.S.; Meena, S.C.; Swami, Saurabh (Annals of Arid Zone, 2023)
Trait specific germplasm is important for altering plant architecture formaximization and stability of the yield. The traits like short duration (early floweringand maturing), branching pattern, pod length, plant height, internode length, pedunclelength and determinacy have contributed substantially in the development of new varietiesin legumes. However, in cluster bean (Cyamopsis tetragonoloba L. Taub.) most of thevarieties embody a similar plant architecture and belong to same maturity group withcomparable yield potential, limiting the scope for further improvement. The economicallyimportant traits like seed weight (test weight ≈3.5 g), pod length (≈6.0 cm), seeds perpod (≈6) and crop duration (≈95 d) have a very narrow range in seed type varieties ofcluster bean. Realizing the paucity of diversity in traits for further yield improvementof yield and suitable plant type in guar efforts were made to identify trait specificgenotypes to serve as donors. Genotypes possessing short life cycle, longer pods, highseed weight and longer seedling have been reported.